2020
DOI: 10.1007/s12035-020-02151-6
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of the Neurogenic Potential in the Rat Inferior Colliculus from Early Postnatal Days Until Adulthood

Abstract: Neural stem cells (NSCs) have been recently identified in the inferior colliculus (IC). These cells are of particular interest, as no casual therapeutic options for impaired neural structures exist. This research project aims to evaluate the neurogenic potential in the rat IC from early postnatal days until adulthood. The IC of rats from postnatal day 6 up to 48 was examined by neurosphere assays and histological sections. In free-floating IC cell cultures, neurospheres formed from animals from early postnatal… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
14
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
1

Relationship

2
4

Authors

Journals

citations
Cited by 6 publications
(14 citation statements)
references
References 65 publications
(90 reference statements)
0
14
0
Order By: Relevance
“…In adult rodents, NSCs have been widely documented in the SVZ and the SGZ [ 21 , 22 ], but the hypothalamus, the neocortex and the inferior colliculus have recently been identified as new potential neurogenic zones [ 23 , 24 , 25 , 26 ]. In these neurogenic regions, quiescent and activated NSCs are present, generating new neurons throughout life [ 25 , 26 , 27 ]. To highlight the potential neurogenic niche status of the vestibular nuclei in physiological conditions, we used a combination of cell markers to identify NSCs.…”
Section: Discussionmentioning
confidence: 99%
“…In adult rodents, NSCs have been widely documented in the SVZ and the SGZ [ 21 , 22 ], but the hypothalamus, the neocortex and the inferior colliculus have recently been identified as new potential neurogenic zones [ 23 , 24 , 25 , 26 ]. In these neurogenic regions, quiescent and activated NSCs are present, generating new neurons throughout life [ 25 , 26 , 27 ]. To highlight the potential neurogenic niche status of the vestibular nuclei in physiological conditions, we used a combination of cell markers to identify NSCs.…”
Section: Discussionmentioning
confidence: 99%
“…Interestingly, significantly lower expression of Sox-2 was present in the single-cell studies of the IC. In contrast, very similar expressions of the two markers were detected in neurospheres of the IC of PND 6 rats [ 41 ]. PND 8 animals were not evaluated in this study, but there was already a significant decrease in ATOH1 compared with PND 12 animals.…”
Section: Discussionmentioning
confidence: 99%
“…The IC showed 5.06 ± 1.12% astrocytic cells. Nestin-positive cells had a very similar expression profile of 13.24 ± 6.07% [ 41 ]. Interestingly, the MGB assumes a critical role in tinnitus pathology, and GFAP expression has been shown to remain stable in the rat tinnitus model compared to the auditory cortex [ 51 ].…”
Section: Discussionmentioning
confidence: 99%
“…Immuno uorescence staining showed that the differential expression of Pnky did not affect the stem fate of C17.2 and NE4C, with the percentage of Nestin-positive cells up to 99% in each stable cell lines (Fig. 1b and f), which indicating the undifferentiated state of NSCs (Engert et al 2021). Further investigations of Pnky on cell proliferation were also carried out using cell counting and EdU assays.…”
Section: Lncrna Pnky Negatively Regulates the Proliferation Of Nscsmentioning
confidence: 92%